Whipple's disease confined to the nervous system. Issue 12 (December 1981) - Pollock, S; Lewis, P D; Kendall, B
Abstract : Whipple's disease confined to the nervous system occurred in a 36-year old woman who presented with grand mal seizures and dementia. There was no evidence of extracerebral involvement and the jejunal biopsy was negative before treatment. Multiple enhancing lesions on CT scan progressed despite therapy with minocycline and prednisone, but resolved on treatment with tetracycline. The dementia did not progress while she was on antibiotic therapy. Whipple's disease should be considered as a treatable cause of progressive dementia even in the absence of an abnormal jejunal biopsy.